Duality of the society «Harmony – disharmony»: a view through the prism of the Quranic revelation (Journal of Philosophy Culture and Political Science, 2018)
This article reveals an understanding of the duality of «spiritual – material» from the point of the Koranic knowledge. A detailed analysis of the complex and significant interrelationships of the duality under investigation with the concepts of harmony and disharmony is given in the article. The basic principle of Islamic dogma is its priority of the transformation of the material into the spiritual. In the presented research the concept of harmony is applied both to the Universe, to the society as well as to an individual. The law of social and economic harmony, which formsd the dominant spiritual needs over the materialneeds and desires of individuals has been put forward as the basic law of the personal life activity and the society. The law of social and economic harmony, which regulates the dominance of spiritual needs over the material needs and individual desires, is put forward as the basic law of the human life activityand society. The combination of harmony and disharmony in various proportions is a regularity of reality at all times which provides that there is a spiritual and moral basis for social evolution. At the same time, each society strives to the predominance of Harmony over disharmonies in the long run. This strategy isaimed at the preservation and development of civilizations, including the economic activities of peoples. The study of socio-economic harmony, its laws and problems in the context of the duality of individual and the society as a whole is the starting point for the sustainable development of countries, for solvingscientific, applied and practical problems. The tasks of overcoming financial, economic, demographic and environmental crises, military-political conflicts and terrorist acts, combating the consequences ofnatural disasters establish partnership relations between states and preserve the civilization. The mostimportant is the conscious use of theoretical positions in human upbringing and training capable of synthesizingtrue spiritual and scientific knowledge, working in the conditions of the duality of the society«Harmony – disharmony» in a new formation.Key words: duality, society, spiritual, material, harmony, disharmony.